Physicochemical Assessment of Khelna Reservoir Water from Aurangabad District of Maharashtra - Sawdekar, J H; Jadhav, M J (Plantae Scientia, 2021)
Present study deals with the physicochemical assessment of Khelna reservoir water. Life in water depends upon the physicochemical conditions prevailing in that water. A total of 20 parameters were analyzed at seasonal intervals. Results of present study reveals that all selected physicochemical parameters were found in normal range as per the guidelines of WHO. The water is potable and safe for drinking and irrigation purpose. In order to maintain better quality of water, regular monitoring of quality of water and protection and conservation of water bodies is required. A proper awareness among society has to be created about protection and conservation of water resources.